Regulation of Macromolecular Biosynthesis in a Mutant of Escherichia coli Defective in Membrane Phospholipid Biosynthesis - Glaser, Michael (National Academy of Sciences, 1973)
Nucleic acid and protein synthesis were studied in temperature-sensitive mutants defective in phospholipid synthesis. The defect is due to a single mutation in glycerol 3-phosphate acyltransferase (EC 2.3.1.15). The results show that at the restrictive temperature not only does phospholipid synthesis cease, but DNA, RNA, and protein synthesis also cease. Active transport continues, however, indicating that the cells do not become leaky or lose their energy supply. These results suggest that phospholipid synthesis is coupled to DNA, RNA, and protein synthesis.